Transversal Kerr Effect Enhancement of Permalloy-Based Shallow Lamellar Magnetoplasmonic Crystals - Dmitry Murzin; Victor Belyaev; Johannes Kern; Corinna Kaspar; Wolfram H. Pernice; Rudolf Bratschitsch; Valeria Rodionova (Photonics, 2022)
This work demonstrates spectral dependencies of reflectivity and the transversal Kerr effect of a series of permalloy magnetoplasmonic crystals based on shallow lamellar diffraction gratings with a period of 500 nm, stripe’s width of 250 nm, and diffraction stripes’ heights of 28, 43, 67, and 88 nm. The fabricated magnetoplasmonic crystals show a monotonic increase of the transversal Kerr effect and the diffraction figure-of-merit with higher diffraction stripes. The maximum achieved modulation value of the transversal Kerr effect was found to be 0.78%, which can be further tuned by the periodicity and stripes width of the magnetoplasmonic crystals.